Work Motivation and Organizational Culture as Determinants of Civil Servant Performance and OCB in Boalemo Regency - M Yusuf Alfian Rendra Anggoro KR; Ismail Rasulong; Sherry Adelia Natsir Kalla; Mansoor Abdul Hamid (Universitas Muhammadiyah Makassar, 2026)
Public sector organizations are increasingly required to improve employee performance and encourage extra-role behavior in order to deliver effective and accountable public services. However, empirical evidence regarding the role of work motivation and organizational culture in shaping employee performance and Organizational Citizenship Behavior remains inconsistent, particularly in regional government institutions. This study aimed to analyze the influence of work motivation and organizational culture on employee performance and Organizational Citizenship Behavior, as well as to examine the mediating role of employee performance in these relationships. The research employed a quantitative research design using a survey approach. The population consisted of civil servants working in the regional government of Boalemo Regency, Indonesia, and respondents were selected using a proportional random sampling technique. Primary data were collected through structured questionnaires and analyzed using Structural Equation Modeling with the Partial Least Squares approach. The results indicated that work motivation had a positive and significant effect on employee performance and Organizational Citizenship Behavior. Organizational culture, however, did not show a significant influence on either employee performance or Organizational Citizenship Behavior. Furthermore, employee performance was found to significantly influence Organizational Citizenship Behavior and partially mediated the relationship between work motivation and Organizational Citizenship Behavior. These findings highlight the importance of strengthening employee motivation to enhance performance and voluntary work behavior in the public sector. The study contributes to the literature on public sector management by providing empirical evidence on the mechanisms linking motivation, performance, and Organizational Citizenship Behavior, and offers practical implications for government institutions seeking to improve organizational effectiveness.